Importance of Green Marketing and its Potential - Dvořáková Líšková, Zuzana; Cudlínová, Eva; Pártlová, Petra; Dvořák, Petr (Slovak University of Agriculture in Nitra, 2016)
Green marketing is possibly the newest type of marketing. Recently, it has also been the most discussed one by organizations, companies and even states. Green marketing tries to produce, promote and recycle products that are friendly to the environment. Green marketing is a global concern and it is going to have a better future. However, this type of marketing meets a few problems such as much effort to replace conventional products and a lack of confidence. Many companies produce and promote such products as much as possible. In spite of this, the public is still sceptical. The paper presents the theoretical important knowledge on green marketing, its definitions, customer behaviour formulas, and its potential.
Keywords: green marketing; behaviour; Eco-product; generation